2016
DOI: 10.1080/19425120.2016.1161682
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Predicting Size Selection in Diamond‐Mesh Cod Ends for Danish Seining: A Study Based on Sea Trials and Computer Simulations

Abstract: Danish seining is an important fishing method used to harvest demersal species. Knowledge about the size selectivity of different demersal species with this type of fishing gear is therefore of importance for managing the exploitation of marine resources. However, there are only limited data on size selection in cod ends in this fishery. Sea trials were therefore carried out to collect size selectivity data for Atlantic Cod Gadus morhua, Haddock Melanogrammus aeglefinus, and Witch Flounder Glyptocephalus cynog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…For complete model details, see Wileman et al (1996), Wienbeck et al (2014), and Herrmann et al (2016). To determine which model best described the data, we evaluated fit statistics for each model.…”
mentioning
confidence: 99%
“…For complete model details, see Wileman et al (1996), Wienbeck et al (2014), and Herrmann et al (2016). To determine which model best described the data, we evaluated fit statistics for each model.…”
mentioning
confidence: 99%
“…Shorter haul durations, shallower fishing grounds and smaller total catches were found in seines than in trawls. Besides the late entry of fish into the net and the corresponding short time within the gear (Herrmann et al., ; Noack et al., ), these are all factors that have positive impact on the survival of discarded fish (van der Reijden et al., ). Previous studies on discard survival focused on different types of trawling such as beam trawling (Depestele, Desender, Benoît, Polet & Vincx, ; van der Reijden et al., ; Uhlmann et al., ) and otter trawling (Methling, Skov & Madsen, ), but no studies have so far investigated discard survival probabilities for Danish seines.…”
Section: Discussionmentioning
confidence: 99%
“…lighter ground gear of seines) and particularly the fishing procedures (Eigaard et al., ; Herrmann, Krag, Feekings & Noack, ), this grouping of seines and trawls has been brought into question by fishers and other stakeholders in the EU. Fishers that operate seines claim a loss of more marketable fish than those using trawls when legal mesh sizes are used (see Herrmann et al., ). This highlights the need for more detailed information about the two gear types and their catches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The codend is the part of towed fishing gears where the catch is collected and where the main selection of fish occurs (Wileman et al, 1996). Therefore, most studies on towed fishing gears, e.g., selectivity studies on trawls (e.g., Reeves et al, 1992;Graham et al, 2004;Frandsen et al, 2010) or Danish anchor seines (e.g., Herrmann et al, 2016;Noack et al, 2017), or survival studies (e.g., Uhlmann et al, 2016), focused on the individuals in or escaping from the codend. Previous studies on the selectivity of commercially valuable crustaceans in different types of trawls, however, found that a substantial part of the selection of Norway lobster (Nephrops norvegicus; Hillis and Earley, 1982), brown shrimp (Crangon crangon; Polet, 2000) and Antarctic krill (Euphausia superba; Krag et al, 2014a) takes place in the forward parts of a trawl net.…”
Section: Introductionmentioning
confidence: 99%